Integrating Real-Time IoT Based Monitoring and Dashboard Design for Closed-House Hen Farming - Handojo, Andreas; Setijarso, Edyq; Halim, Siana; Octavia, Tanti (Institute of Research and Community Outreach - Petra Christian University, 2025)
This paper presents a comprehensive solution that integrates IoT-based hardware systems with a real-time dashboard specifically designed for closed-house poultry farming, focusing on laying hens. Since laying hens are homeothermic animals, they are sensitive to temperature and humidity. Therefore, it is essential to monitor and control these environmental factors, along with ventilation, in real time. We describe a smart monitoring system that combines sensors, microcontrollers, and Android-based dashboards to provide actionable insights into poultry health and egg production performance. This system tracks various parameters, including temperature, humidity, equipment status, and key production indicators such as Hen Day Production (HDP), Hen House Production (HHP), and Feed Conversion Ratio (FCR). Evaluations conducted with local poultry farmers have shown improved awareness, usability, and the potential for increased operational efficiency. Despite some limitations, the dashboard provides a clear overview and helps inform decisions aimed at enhancing conditions and boosting egg production. This tool enables breeders to monitor and improve the performance of their laying hens and manage feeding strategies effectively. Additionally, it can assist in controlling and enhancing the closed-house environments and ventilation systems. The system's performance and usability were evaluated through User Acceptance Testing (UAT) and production Key Performance Indicators (KPIs), confirming its potential to enhance operational efficiency.